Overexpression of the cotton trihelix transcription factor GhGT23 in Arabidopsis mediates salt and drought stress tolerance by binding to GT and MYB promoter elements in stress-related genes - Li, Yue; Hu, Ziyao; Dong, Yongmei; Xie, Zongming (Frontiers in Plant Science, 2023)
Cotton (Gossypium hirsutum L.) is the world’s most economically valuable textile crop. However, cotton plants are often subjected to numerous abiotic stresses that can dramatically limit yield. Trihelix transcription factors (TTFs) play important roles in abiotic stress responses in many plant species, and efforts to better understand their roles in cotton abiotic stress responses are ongoing. In this study, a member of the cotton TTF family (GhGT23) was functionally characterized. This protein contains a SANT domain and is a member of the SIP subfamily of TTF proteins. GhGT23 was significantly (p < 0.05) and highly expressed in cotton fiber compared to relatively low expression in other tissues. A significant (p < 0.05) increase in GhGT23 expression occurred in cotton seedlings within 12 hours of drought, salt, and ABA exposure. The GhGT23 protein localized in the nucleus but exhibited no signs of transactivation activity. GhGT23 overexpression in Arabidopsis conferred enhanced drought and salt stress tolerance. The expression of stress-related genes was higher in transgenic Arabidopsis expressing GhGT23 than in wild-type plants subjected to salt stress. The results of electrophoretic mobility shift assay revealed that GhGT23 could bind to the GT cis-elements GT-1Box (Box II), GT2-Box, GT3-Box, GT-3a (Site1-type), GT-3b, and Box as well as the MYB cis-elements MBS1 and MRE4. Our results demonstrate that GhGT23 positively regulates salt and drought stress responses, possibly by enhancing the expression of stress-related genes.